Cost of postoperative complications after general surgery at a major Canadian academic centre. (27th September 2022) - Roach, Eileen; de la Maza, Luis; Rieder, Scott; Vigneswaran, Laavanyah; Maeda, Azusa; Okrainec, Allan; D Jackson, Timothy
Abstract: Background: In a fiscally constrained health care environment, the need to reduce unnecessary spending is paramount. Postoperative complications contribute to hospital costs and utilization of health care resources. Objective: The purpose of this observational study was to identify the cost associated with complications of common general surgery procedures performed at a major academic hospital in Toronto, Ontario. Methods: The institutional National Surgical Quality Improvement Program database was used to identify complications in patients who underwent general surgical procedures at our institution from April 2015 to February 2018. A mix of elective and emergent cases was included: bariatric surgery, laparoscopic appendectomy, laparoscopic cholecystectomy, thyroidectomy, right hemicolectomy and ventral incisional hernia repair. The total cost for each visit was calculated by adding all the aggregate costs of inpatient care. Median total costs and the breakdown of cost components were compared in cases with and without complications. Results: A total of 2713 patients were included. Nearly 6% of patients experienced at least one complication, with an incidence ranging from 1.1% after bariatric surgery to 23.8% after right hemicolectomy. The most common type of complication varied by procedure. Median total costs were significantly higher in cases with complications, with a net increase ranging from $2989 CAD (35% increase) after bariatric surgery to $10 459 CAD (161% increase) after ventral incisional hernia repair. Conclusion: Postoperative complications after both elective and emergent general surgery procedures add substantially to hospital costs. Quality improvement initiatives targeted at decreasing postoperative complications could significantly reduce costs in addition to improving patient outcomes.